2015
DOI: 10.1017/s0022215115000560
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors that affect the Fukuda stepping test in normal participants

Abstract: Our results suggest that certain alterations to the test environment may improve the sensitivity of this clinical examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 11 publications
(26 reference statements)
3
14
0
3
Order By: Relevance
“…Secondly, women seek more medical care than men 19 . Nonetheless, we chose not to divide the results by sex, because no previous studies have indicated that the patient's sex can interfere with the UFT 12,22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondly, women seek more medical care than men 19 . Nonetheless, we chose not to divide the results by sex, because no previous studies have indicated that the patient's sex can interfere with the UFT 12,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have performed only the closedeyes step, disregarding the open-eyes one 12,16,17,22 . However, none of these studies justified the exclusion of the open-eyes step, although traditional texts do all assert that closed-eyes balance tests are more sensitive 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En adultos se reporta el uso de las escalas de Romberg, Test de Berg. Mini BEStest, BEStest y fukuda test, estos se encargan de predecir riesgo de caída en pacientes con alteraciones neuromusculares, osteomusculares y vestibulares (Agrawal, 2011) (Benka Wallen, 2016) (Honaker, 2009) (Hong, 2015) (Munnings, 2015) (O'Hoski, 2015 (Saso, 2016) (Tsang, 2013) (Zhang, 2011). En población pediátrica se utiliza la escala Pediatric balance scale en pacientes con parálisis cerebral para la evaluación de las respuestas selectivas de balance en niños (Darr, 2015) (Lim, 2015).…”
Section: Balanceunclassified